Facilitating CAD/CAM nasoalveolar molding therapy with a novel click-in system for nasal stents ensuring a quick and user-friendly chairside nasal stent exchange - Grill, Florian D.; Ritschl, Lucas M.; Dikel, Hannes; Rau, Andrea; Roth, Maximilian; Eblenkamp, Markus; Wolff, Klaus-Dietrich; Loeffelbein, Denys J.; Bauer, Franz X. (Scientific Reports, 2018)
Nasoalveolar molding (NAM) aims to improve nasal symmetry with a nasal stent in cleft lip and palate (CLP) patients. When plates have to be exchanged because of dentoalveolar growth or cleft reduction, the nasal stent has to be mounted onto a new plate. This procedure elongates visiting hours for patients and parents or requires second treatment sessions. This study introduces a quick-lock additive manufacturing solution for chairside nasal stent exchange called RapidNAM. A novel taping retention pin has been designed that enables nasal stent insertion. Patients with unilateral CLP were included in this study. Plaster models were digitalized and measured by two independent observers. Two methods of CAD/CAM-molding therapies were compared: (i) conventional adhesion of a nasal stent (CAD/CAM NAM); (ii) quick-lock system in which the nasal stent was transferred to another plate (RapidNAM). CAD/CAM NAM and its refinement RapidNAM significantly increased the cleft-side nasal height and tilted the nose towards symmetry. The quick-lock system minimizes wire adaptations, since the preexisting stent can be reused. The new nasal stent development seems a feasible solution to minimize visiting hours but with clinically satisfactory results. This new nasal stent system combines traditional elements of NAM with CAD/CAM-technology.
EVALuna2:35084